Coastal Community Behavior Patterns Related to Hypertension Treatment: A Case Study - Dian Ayu Irhamna; Fahmi Ichwansyah; Meutia Zahara (GLOBAL HEALTH SCIENCE GROUP, 2025)
Hypertension is a high-risk non-communicable disease and is known as a